2016
DOI: 10.1021/acssuschemeng.6b00774
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lignin Features on Thermal Stability and Mechanical Properties of Natural Rubber Compounds

Abstract: The aim of this work is to elucidate the relationship between lignin main features and its behavior in natural rubber compounds, in particular focusing on thermal stability and mechanical properties. Five lignins obtained from different sources and through different extraction processes were characterized in terms of purity, sulfur content, molecular weight distribution (GPC), qualitative and quantitative functional group distribution (FTIR and 31 P-NMR). Then the lignins were incorporated in natural rubber by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 40 publications
(87 reference statements)
1
91
0
Order By: Relevance
“…A strong band related to the C-O stretching of aliphatic alcohols and ether was found at 1024 cm -1 . It appeared in all spectra and it reflected the presence of polysaccharides (Barana et al 2016a). In the same region it is possible to find the Si-O stretching (around 1000 cm -1 ) related to the presence of silicate as inorganic fraction (Barana et al, 2016b).…”
Section: Characterization Of the Lignocellulosic Materialsmentioning
confidence: 91%
See 1 more Smart Citation
“…A strong band related to the C-O stretching of aliphatic alcohols and ether was found at 1024 cm -1 . It appeared in all spectra and it reflected the presence of polysaccharides (Barana et al 2016a). In the same region it is possible to find the Si-O stretching (around 1000 cm -1 ) related to the presence of silicate as inorganic fraction (Barana et al, 2016b).…”
Section: Characterization Of the Lignocellulosic Materialsmentioning
confidence: 91%
“…It also absorbs UV radiation and exhibits flame-retardant properties (De Chirico et al 2003). Furthermore, lignin can be used in epoxy resins (Lora and Glasser 2002), green composites (Bertini et al 2012;Thakur et al 2014), and as filler in tires (Frigerio et al 2014;Barana et al 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Lignin is included in rubber products to enhance their properties and also lower their prices (Kumaran and De, 1978;Botros et al, 2006;Feldman, 2016). However, previous studies of lignin-filled rubbers revealed the incompatibility of polar lignin and nonpolar rubber (Setua et al, 2000;Kosikova et al, 2007;Barana et al, 2016). This has generated further study of the incorporation of lignin into the rubber matrix by using various mixing methods and modifications to achieve better performance.…”
Section: Lignin As a Natural Alternative Sourcementioning
confidence: 99%
“…A lot of approaches have been taken by researchers to improve the process of rubber compound preparation and enhance the flexibility of the final composites (Vieira et al, 2011). One approach to utilize lignin for rubber application is by using simple blending with a rubber matrix (Shukla et al, 1998;Setua et al, 2000;Botros et al, 2006;Barana et al, 2016). However, such rubber compounds suffered from low compatibility and poor disperse-ability.…”
Section: Lignin As a Natural Alternative Sourcementioning
confidence: 99%
“…Barana et al extracted lignin from different sources and by different processes was incorporated in NR. They observed that difference in the chemical and morphological characteristics of lignin influence its antioxidant and reinforcement capability [28]. Davidson et al recovered SBR from its aqueous polymerization emulsion by coagulation with acid and a lignin compound.…”
Section: Introductionmentioning
confidence: 99%